2011
DOI: 10.1103/physreva.84.043406
|View full text |Cite
|
Sign up to set email alerts
|

Classical model of the upper bounds of the cascading contribution to the second hyperpolarizability

Abstract: We investigate whether microscopic cascading of second-order nonlinearities of two molecules in the side-by-side configuration can lead to a third-order molecular nonlinear-optical response that exceeds the fundamental limit. We find that for large values of the second hyperpolarizability, the side-by-side configuration has a cascading contribution that lowers the direct contribution. However, we do find that there is a cascading contribution to the second hyperpolarizability when there is no direct contributi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…(17) and (20)- (25) are first-order corrections to the response of molecules that are polarized along the direction of the applied field. With a more rigorous approach, one can find the effective (hyper)polarizabilities for all possible components.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(17) and (20)- (25) are first-order corrections to the response of molecules that are polarized along the direction of the applied field. With a more rigorous approach, one can find the effective (hyper)polarizabilities for all possible components.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are larger cascading enhancements at higher concentration, we consider a hexagonal close-packed structure with a center-of-mass separation distance of approximately 10.04Å. [28] Note that a past study showed that perturbed energy states from cascaded molecules have small effects on large off-resonant nonlinear optical responses, [17] where we only observe significant effects after the molecules have passed into the "forbidden" zone in which they spatially overlap.…”
Section: Real Systems: Monolayers Of Close-packed C60mentioning
confidence: 99%
See 2 more Smart Citations
“…A similar type of coupling can be exploited to enhance second order hyperpolarizabilities, in which connection such an interaction is referred to as cascading. 18 Our present results lead to a detailed analysis on the symmetry constraints and selection rules governing the emergence of proximity-induced Raman signals. a) david.andrews@physics.org…”
Section: Introductionmentioning
confidence: 99%